Study on the influence of training at altitute (2000m) on the blood hemoglobin and erythropoietin values in athletics (aerobic rsistance) - Man, M. C.; Ganera, C. (Science, Movement & Health, 2015)
Aim. Training at altitude as factor of progress in the preparation of the endurance athletes has become a concern for researches, once with the Olympic Games in Mexico from 1968 at an altitude of 2200m. The research aims to achieve a significant increase in blood hemoglobin and erythropoietin (EPO) values in the athletes` body, after introducing in the training plan a preparatory stage of 21 days at altitude. Methods. The research has been conducted on a group of 10 competitive athletes during a training stage of 21 days in the `Piatra Arsã` National Sports Complex of the Bucegi Mountains, situated at an altitude of 2000 m. In order to carry out this research we have used the experimental method and the laboratory analysis method, the staticmathematical method and the graphical representation method. Results. The data analysis has shown an increase in the hemoglobin values, by an average of 0,64g/dl namely with 4,4%, and of the erythropoietin with 1,37UI/l namely with 26,5% in terms of performing the altitude training stage. Conclusions. Performing one or more altitude training stages, significantly improves the performance of the runners by triggering some physiological, hematologic changes in the athletes` body favorable to performance increase.